Mladinska fantastična pripoved in njena umestitev v koncept sodobne slovenske mladinske fantastične proze - Artnik, Gregor (Revija za elementarno izobraževanje, 2012)
This paper is an attempt to issue a challenge to genre typology of contemporary Slovenian fantastic prose for youth based on preliminary treatment of contemporary fantastic tale and related terminology. Its foundation is placed in thematic and structural characteristics of fantastic literature as supergenre. Regardless of the fact that Slovenian fantastic tale is often not as extensive as related texts in Western literature, there are also indications of genre fluidity which in the core of contemporary Slovenian fantastic tale for youth often merges mutually exclusive elements of dystopia, fantasy, horror, myth and science fiction.
Keywords: Slovene literature; Slovenian literature; slovenska književnost; fantastic prose; fantastična proza; tipologija; typology; young adult literature; mladinska književnost